2015
DOI: 10.1016/j.trc.2015.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Marginal cost congestion pricing based on the network fundamental diagram

Abstract: Congestion pricing schemes have been traditionally derived based on analytical representations of travel demand and traffic flows, such as in bottleneck models. A major limitation of these models, especially when applied to urban networks, is the inconsistency with traffic dynamics and related phenomena such as hysteresis and the capacity drop. In this study we propose a new method to derive time-varying tolling schemes using the concept of the Network Fundamental Diagram (NFD). The adopted method is based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 38 publications
3
49
0
Order By: Relevance
“…Recently, several works (Zheng et al, 2012;Simoni et al, 2015) are devoted to develop effective congestion pricing schemes similar to the one of Section 2.2, however without treating multimodality or user heterogeneity. Operating at a decent level of public transport (PT) services is important.…”
Section: Pricing Strategies With Accessibility Improvement and Incentmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several works (Zheng et al, 2012;Simoni et al, 2015) are devoted to develop effective congestion pricing schemes similar to the one of Section 2.2, however without treating multimodality or user heterogeneity. Operating at a decent level of public transport (PT) services is important.…”
Section: Pricing Strategies With Accessibility Improvement and Incentmentioning
confidence: 99%
“…In this work, travelers could only change their time of departure and route but mode choice is not an option. A similar approach was later applied in Simoni et al (2015) who derived optimal pricing using MFD and marginal cost theory, without investigating the impact of pricing on multimodality either. Combining dynamic pricing with dynamic allocation of road space between multiple modes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…MFD-based traffic management strategies serve for this sustainable and global mobility goal. Recent studies have demonstrated the performance of such strategies, examples including congestion pricing (Zheng et al, 2012;Simoni et al, 2015), space allocation for bus lanes (Zheng and Geroliminis, 2013), and dynamic traffic signal perimeter control (refer to Ramezani et al, 2015 for a review).…”
Section: Parking Pricing Strategiesmentioning
confidence: 99%
“…See Aboudolas and Geroliminis (); Geroliminis et al. (); Keyvan‐Ekbatani, Kouvelas, Papamichail, and Papageorgiou (); Ramezani, Haddad, and Geroliminis () for NFD‐based perimeter control, and Gu, Shafiei, Liu, and Saberi (); Simoni, Pel, Waraich, and Hoogendoorn (); Zheng, Rérat, and Geroliminis (); Zheng, Waraich, Axhausen, and Geroliminis () for NFD‐based pricing.…”
Section: Introductionmentioning
confidence: 99%
“…To address this network design problem with an expensive‐to‐evaluate objective function featuring nonconvexity, nonlinearity, and nonclosed form, simulation optimization (SO) or simulation‐based optimization has recently been investigated and advocated (Amaran, Sahinidis, Sharda, & Bury, ; Osorio & Bierlaire, ). When SO is applied to solve the TLP, existing methods can be classified into two broad categories of feedback control (Gu, Shafiei, et al., ; Simoni et al., ; Zheng et al., ; Zheng et al., ) and surrogate‐based optimization (Chen et al., ; Chen, Xiong, He, Zhu, & Zhang, ; Chen, Zhang, He, Xiong, & Zhu, ; Chow & Regan, ; Ekström, Kristoffersson, & Quttineh, ; He, Chen, Xiong, Zhu, & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%